Catechol derived from aronia juice through lactic acid bacteria fermentation inhibits breast cancer stem cell formation via modulation Stat3/IL‐6 signaling pathway. Issue 11 (18th July 2018) - Choi, Hack S.; Kim, Ji‐Hyang; Kim, Su‐Lim; Deng, Hong‐Yuan; Lee, Doseung; Kim, Chang Sook; Yun, Bong‐Sik; Lee, Dong‐Sun
Abstract : Cancer stem cells (CSCs) as a subpopulation of cancer cells are drug‐resistant and radiation‐resistant cancer cells to be responsible for tumor progress, maintenance and recurrence of cancer, and metastasis. This study isolated and investigated a new cancer stem cell (CSC) inhibitor derived from lactic acid fermentation products using culture broth with 2% aronia juice. The anti‐CSC activity of aronia‐cultured broth was significantly higher than that of the control. Activity‐guided fractionation and repeated chromatographic preparation led to the isolation of one compound. Using nuclear magnetic resonance and ESI mass spectrometry, we identified the isolated compound as catechol. In this study, we report that aronia‐fermented catechol has a novel inhibitory effect on human breast CSCs. Catechol inhibited breast cancer cell proliferation and mammosphere formation in a dose‐dependent manner. This compound reduced the CD44 high /CD24 low subpopulation, ALDH‐expressing cell population and the self‐renewal‐related genes nanog, sox2, and oct4 . Catechol preferentially reduced mRNA transcripts and protein levels of Stat3 and did not induce c‐Myc degradation. These findings support the novel utilization of catechol for breast cancer therapy via the Stat3/IL‐6 signaling pathway. Our results suggest that catechol can be used for breast cancer therapy and that Stat3 expression is a marker of CSCs. Catechol inhibited Stat3 signaling by reducing Stat3 expression and secreted IL‐6, a CSC survival factor. These findings support the novel utilization of catechol for breast cancer therapy via Stat3/IL‐6 signaling.